Studying social policy and resilience to adversity in different welfare states: Britain and Sweden. - Jones, C; Burström, B; Marttila, A; Canvin, K; Whitehead, M (2006)
Is poverty more damaging to health in Britain than in Sweden, and if so, why? Following previous research by the authors that suggested such an effect, a new comparative study is examining whether there are aspects of the social and policy context in Britain that add to and reinforce the health-damaging experience of being poor. Conversely, are there other aspects of living in Sweden that are supportive for people in poverty, which make the experience of poverty less stressful and health-damaging? Stemming from this ongoing study, the aim of this article is to present a framework for understanding the context in which social welfare policies are formed and operate in Britain and Sweden. It then uses the framework to consider the "upstream" influences of ideology, culture, and values on policy development in the two countries and what these developments might mean for the health and well-being of people facing financial adversity in the two societies.